Pelatihan “Remaja Cerdas Kelola Uang, Tanpa Drama” Bagi Remaja Vihara Dhamma Bhakti Tangerang - Sutandi, Sutandi; Hidayat, Adrian; Donny yana; Irwan Irwan; Salikim Salikim; Octavianti Purnama; Erizka Trinurfa Yuliadi; Marselia Purnama (Jurnal Pelayanan Masyarakat, 2026)
This community service aims to improve financial literacy among youth at Vihara Dhamma Bhakti Tangerang. The main problem faced is the lack of understanding among teenagers in distinguishing between needs and wants, as well as the risk of being trapped in a consumptive lifestyle in the digital era. The implementation method was carried out through a one-day interactive training including material presentation, discussion, and budget preparation simulation. The results showed a significant increase in participants' understanding, where 100% of respondents stated they understood how to manage finances to avoid fraud. In addition, participants were able to prepare independent financial plans based on their pocket money.